2005
DOI: 10.1007/s10067-005-1106-9
|View full text |Cite
|
Sign up to set email alerts
|

Seronegative spondyloarthropathies in Greece: a population-based study of prevalence, clinical pattern, and management. The ESORDIG study

Abstract: The objective of this study was to determine the prevalence, clinical pattern, and management of seronegative spondyloarthropathies (SpA) in the general adult population of Greece. This population-based study was conducted on a target adult (> or =19-year-old) population of 14,233 subjects by rheumatologists who visited households in nine dispersed areas. An interview (standardized questionnaire) was conducted, clinical evaluation and laboratory investigation were done, and established diagnostic classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 15 publications
7
41
2
3
Order By: Relevance
“…The diagnostic criteria we used allow the inclusion of both active and inactive cases. Although Table 3 The results of HLA-B27 and HLA-B51 in the studied population and comparison the results in the other regions in our country (% frequencies) Pirim (121) Uyar ( [40,[72][73][74] 0-0.8 [75] 0.06-0.54 [46-48, 54, 76] 0.1-6.3 [60,75] 0.49 [12] 0.120 0.114-0.126 IBD 0.20-0.42 [77,78] 0.31 [79] 0.16 [80] 0.3-0.5 [81][82][83] 0.035 0.032-0.037 Ps 1.17-4.20 [84][85][86][87][88] 0.67 [56,89] 0.424 0.414-0.434…”
Section: Rheumatoid Arthritismentioning
confidence: 97%
“…The diagnostic criteria we used allow the inclusion of both active and inactive cases. Although Table 3 The results of HLA-B27 and HLA-B51 in the studied population and comparison the results in the other regions in our country (% frequencies) Pirim (121) Uyar ( [40,[72][73][74] 0-0.8 [75] 0.06-0.54 [46-48, 54, 76] 0.1-6.3 [60,75] 0.49 [12] 0.120 0.114-0.126 IBD 0.20-0.42 [77,78] 0.31 [79] 0.16 [80] 0.3-0.5 [81][82][83] 0.035 0.032-0.037 Ps 1.17-4.20 [84][85][86][87][88] 0.67 [56,89] 0.424 0.414-0.434…”
Section: Rheumatoid Arthritismentioning
confidence: 97%
“…Three population-based studies reported on the prevalence of spondyloarthritis including PsA in the past 3 years [10][11][12]. In Greece, Trontzas et al [10] clinically assessed 10,647 individuals. Using the ESSG criteria, they estimated the prevalence of PsA in Greece to be 0.17%.…”
Section: Prevalence Of Psoriatic Spondylitismentioning
confidence: 99%
“…Data were not population-based, for they were obtained by examining diagnoses among rheumatology hospitals and private rheumatologists. In another study evaluating, on a population base, the prevalence of seronegative spondyloarthropaties in different geographical areas of Greece, a prevalence of 0.17% was shown (27). The prevalence was higher in men and in the age class between 49 and 68 years.…”
Section: Prevalencementioning
confidence: 99%